2017
DOI: 10.1371/journal.pone.0174455
|View full text |Cite
|
Sign up to set email alerts
|

Most women recover from psychological distress after postoperative complications following implant or DIEP flap breast reconstruction: A prospective long-term follow-up study

Abstract: BackgroundSubstantial complication rates after postmastectomy breast reconstruction (BR) in breast cancer patients have been reported. Few studies have reported on the resulting psychological distress (PD) and satisfaction with the aesthetic result in relation to postoperative complications after completion of implant or DIEP flap BR. The present study investigated whether women were able to recover from complication related distress in the long term.MethodsPD was prospectively measured using questionnaires re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
15
2
1
Order By: Relevance
“…Furthermore, it was found that the reconstruction group had both the highest increase in emotional functioning and an insigni cant decline in psychosocial wellbeing between baseline and a year after surgery. This is in contrast to the ndings from other studies, which found that women who receive breast reconstruction have more mood disturbances and distress than those who undergo mastectomy, up to twelve months after baseline [6,12,[30][31][32]. Perhaps, the difference between previous research and the current study's ndings can be accounted for by differences in practices regarding patient-centered care.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that the reconstruction group had both the highest increase in emotional functioning and an insigni cant decline in psychosocial wellbeing between baseline and a year after surgery. This is in contrast to the ndings from other studies, which found that women who receive breast reconstruction have more mood disturbances and distress than those who undergo mastectomy, up to twelve months after baseline [6,12,[30][31][32]. Perhaps, the difference between previous research and the current study's ndings can be accounted for by differences in practices regarding patient-centered care.…”
Section: Discussioncontrasting
confidence: 99%
“…If that is the case, and patients would have preferred this treatment option, patients should be given space and enough time to express disappointments, ask questions about other possibilities and process any loss of control. Breast reconstruction, on the other hand, is often a product of choice [12,[30][31][32][33][34]. However, the experience of women undergoing reconstruction may vastly differ based on the timing of reconstruction after mastectomy, type of reconstruction, and the occurrence of surgery-related complications [6,12,30,31,34].…”
Section: Clinical Implications and Conclusionmentioning
confidence: 99%
“…Although the technical success rates of further reconstructive surgery are high, few studies have included patient‐reported outcomes (PROs) in their assessment of success. The value of existing PRO questionnaires in this group, however, is questionable, as previous questionnaire‐based breast reconstruction studies have suggested that complications, including implant loss, do not adversely affect women's long‐term quality of life, in stark contrast to the present findings. This may be because patients with complications such as reconstructive failure do not self‐identify as having had a reconstruction, so elect not to participate; a number of additional reasons for response bias in breast reconstruction studies have been reported recently.…”
Section: Discussioncontrasting
confidence: 92%
“…Women experience breast reconstruction (flap) failure as an emotionally very difficult life event, 36 although previous studies have shown that physical and mental health after a breast reconstruction complication generally recover to normal levels after a period. 37,38 By measuring health-related quality of life using multiple, validated patient-reported outcome measures in a large sample of patients following different types of breast cancer surgery, we were able to improve earlier, smaller, and less consistent attempts to assess health-related quality of life in surgically treated breast cancer patients. Our statistically significant results confirm the findings of studies mentioned previously, 15,20,22,32,35 thereby supporting the added value of breast conservation and reconstruction for breast cancer patients.…”
Section: Plastic and Reconstructive Surgery • July 2020mentioning
confidence: 99%